Pelvicalyceal system duplication with ectopic ureter – diagnostic difficulties associated with the imaging procedure. Two cases report - Agnieszka Pukajło-Marczyk; Anna Jakubowska; Katarzyna Kiliś-Pstrusińska; Anna Biel; Ewa Laska; Danuta Zwolińska (Pediatria i Medycyna Rodzinna, 2014)
Urinary tract abnormalities are the most frequently occurring developmental anomaly in children. Pelvicalyceal system duplication is one of them and signifies the existence of two urine diverting separate systems. This anomaly occurs in 10% of population, usually in girls, and is associated with complete or partial ureter duplication. The frequency of total ureter duplication, which in 20–40% of patients is found as bilateral, is 1:125 children (0.8% of the population). The most frequent malformation is asymptomatic, diagnosed coincidentally casually and does not require any treatment. In some patients with pelvicalyceal system duplication, vesicoureteral reflux (VUR) and ectopic ureter may coexist. Malposition of ureter’s orifice into the bladder predispose to urinary retention, development of hydronephrosis and urinary tract infection (UTI). Ectopic ureterocele is recognized in 6–20% of children with recurrent UTI. The reason why children are referred to the hospital is UTI or hydronephrosis revealed by ultrasound imaging. When the ultrasound image of pelvicalyceal system duplication is ambiguous, micturating cystourethrography (MCU) and scintigraphy become the primary diagnostic procedure, or urography – in more complicated cases. In the case of ectopic ureter, the danger of inappropriate catheterization, i.e. directly into its lumen, may occur. Though very rare, this may cause some diagnostic difficulties and lead to injury of the urinary tract. For this reason, we want to further discuss this complication following a diagnostic procedure on the example of two cases of pelvicalyceal system duplication with ectopic ureter.